Evolution of Hotel Classification System in Russian Federation - KOZLOV, Dmitry Aleksandrovich (Journal of Environmental Management and Tourism; Vol 12 No 1 (2021): JEMT 1(49) Spring 2021DO - 10.14505//jemt.v12.1(49).24, 2021)
The main aim of this paper is to analyze the approaches to the system of classification of accommodation facilities in the Russian Federation. The United Nations World Tourism Organization pays great attention to the unification of classification systems for accommodation facilities in all countries of the world, issuing appropriate recommendations on tourism statistics systems, classification of economic activities, as well as criteria for interregional harmonization. In the Russian Federation, there are a number of laws, regulations, state standards, building and sanitary norms and rules concerning the classification of accommodation facilities. They are so imperfect that they have to be revised almost annually or even several times a year. The general statistics of accommodation facilities currently do not correspond to world recommendations. The classification system needs to be revised and brought into line with international standards as much as possible.